Implementasi Kenaikan Suku Bunga Kredit dan Investasi terhadap Pertumbuhan Ekonomi di Sumatera Utara - Yanti Masryana Sianturi; Chelsya Olyza Malau; Nadia Enjel Lina Silalahi; Anggun Sibarani (Journal Economic Excellence Ibnu Sina, 2024)
The aim of this research is to see how increases in credit and investment interest rates impact economic growth in North Sumatra from 2013 to 2023. Indonesia faces the challenge of balancing economic growth, price stability and job creation as a developing country. Quantitative methods were used in this research, which used secondary data from the National Center for Statistics. This method is multiple linear regression analysis. Included in the variables studied are economic growth, investment, and credit interest rates. The research results show that credit interest rates have a positive but insignificant impact on economic growth, while investment has a negative and significant impact. According to multiple regression analysis, fluctuations in credit and investment interest rates can be responsible for 37.9% of economic growth. Additional unexamined factors influence the remaining sections. This research suggests that the government and stakeholders re-evaluate investment strategies to encourage sustainable economic growth in North Sumatra.